Single nucleotide polymorphisms in IL-1A RS1800587, IL-1B RS1143634 and vitamin D receptor rs731236 in stage III grade B/C periodontitis - ÖZTÜRK ÖZENER, HAFİZE; ASLAN, BEGÜM; AĞRALI, ÖMER BİRKAN; ULUCAN, KORKUT; YILDIRIM, HATİCE SELİN; KURU, LEYLA (My University, 2022)
The purpose of the study is to determine the prevalence of interleukin (IL)-1A (rs1800587), IL-1B (rs1143634) and vitamin D receptor (VDR) (TaqI, rs731236) gene polymorphisms in the Turkish population and their association with Stage III Grade B/C periodontitis. Systemically and periodontally healthy individuals (N = 100) and Stage III Grade B/C periodontitis patients (N=100) based on clinical and radiographic examination were included in this research. Clinical attachment level, probing depth, bleeding on probing, plaque and gingival indices of the subjects were measured. Genotyping of IL-1A (rs1800587), IL-1B (rs1143634) and VDR (rs731236) polymorphisms was conducted by Real Time PCR. Allelic and genotypic distributions of IL-1A (rs1800587) gene polymorphism were not associated with periodontitis (p > 0.05). In IL-1B (rs1143634) gene polymorphism, the C allele was detected more frequently in healthy individuals compared with the periodontitis patients (p=0.045). CC genotype and C allele in VDR (rs731236) gene polymorphism was higher in periodontitis patients (p=0.031, p=0.034, respectively). In comparison with Grade B periodontitis patients and healthy subjects, CC genotype and C allele were observed more frequently in the Grade B periodontitis in terms of alleles (C/T) and genotypes for VDR (rs731236) polymorphism (p=0.024, p=0.008, respectively). This study presents that the VDR (rs731236) polymorphism are associated with enhanced susceptibility to Stage III periodontitis in the Turkish population. Furthermore, VDR (rs731236) polymorphism may be used as an identification criteria to discriminate Grade B and Grade C in Stage III periodontitis.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Genetik; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Medical Genetics; Life Sciences; Molecular Biology and Genetics; Health Sciences; Natural Sciences; GENETİK VE KALITIM; Yaşam Bilimleri (LIFE); GENETICS & HEREDITY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); Genetik (klinik); Moleküler Biyoloji; Genetik; Genetics (clinical); Molecular Biology; Genetics; Interleukin-1alpha; Interleukin-1beta; Vitamin D receptor; Periodontitis; Polymorphism; INTERLEUKIN-1 GENE POLYMORPHISMS; PERI-IMPLANT DISEASES; AGGRESSIVE PERIODONTITIS; SUSCEPTIBILITY TEST; ASSOCIATION; CLASSIFICATION; CLUSTER; SAMPLE; RISK